Analisis Potensi Kandungan Tanaman Obat untuk Menunjang Kesehatan Santri - Husnul Jannah; Masiah Masiah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
Research on the potential analysis of medicinal plant content has been carried out to support the health of students at the Nurul Islam Sekarbela Islamic Boarding School, Mataram City. Primary data collection is carried out by involving the community through interviews with local community groups and individual community members. The selection criteria were based on the informants' abilities and traditional medical practices. In data collection, the interview technique used was